Effect of vitamin C on weight and hematology of tambaqui - Chagas, Edsandra Campos; Val, Adalberto Luís (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to estimate the effect of L-ascorbic acid (vitamin C) dietary supplementation on the body weight and on the hematology of juveniles tambaqui, Colossoma macropomum. After ten weeks receiving diets containing 0, 100 and 500 mg of L-ascorbic acid per kg of food, the fish were netted from the tanks, immediately anesthetized and blood was withdrawn from caudal vein for analysis of hematological parameters. Animals fed on higher ascorbate levels showed higher final body weight, better feed conversion rate and survival. Also, the L-ascorbic acid free-diet resulted in reduction of hematocrit and red blood cell count, characterizing anemia, and an increase of mean cell volume, mean cellular hemoglobin and mean cellular hemoglobin concentration. These results show the importance of L-ascorbic acid supplementation in the diet of juveniles tambaqui. The level of 100 mg of L-ascorbic acid/kg diet is adequate, guaranteeing better body weight gain and maintenance of organic homeostasis.